European ornamental garden flora as an invasion debt under climate change. Issue 5 (5th July 2018) - Haeuser, Emily; Dawson, Wayne; Thuiller, Wilfried; Dullinger, Stefan; Block, Svenja; Bossdorf, Oliver; Carboni, Marta; Conti, Luisa; Dullinger, Iwona; Essl, Franz; Klonner, Günther; Moser, Dietmar; et al.
Abstract: Most naturalised and invasive alien plant species were originally introduced to regions for horticultural purposes. However, many regions now face an invasion debt from ornamental alien species, which have not yet naturalised. In this regard, climate change represents a threat as it may lower the barriers to naturalisation for some ornamental alien species. Identifying those species is extremely important for anticipating impending invasions. To identify predictors of naturalisation, we modelled the effects of climate, nursery availability and species characteristics on the current European naturalisation success of 2, 073 ornamental aliens commonly planted in European gardens. We then used the resulting model together with climate projections for 2050 to forecast future naturalisation risks for the 1, 583 species not yet naturalised in Europe. We found that non‐European naturalised range size, climatic suitability, propagule pressure, having a dioecious sexual system and plant height jointly explained current naturalisation success in Europe. By 2050, naturalisation probability projections increased by more than 0.1 for 41 species, and only decreased by more than 0.1 for one species. Policy implications . Using predictions based on our integrated model of alien ornamental naturalisation success, we identified species with high future naturalisation risk and species with high projected increases in naturalisation potential in Europe under climate change. This species list allows for prioritisation of monitoring and regulation of ornamental plants to mitigate the invasion debt.